1984
DOI: 10.1148/radiology.153.3.6387792
|View full text |Cite
|
Sign up to set email alerts
|

The fetal cisterna magna.

Abstract: Antenatal sonography routinely images the fetal cisterna magna. The identification of a prominent cisterna magna on a routine antenatal sonogram performed for obstetric indications may raise the question of a congenital posterior fossa lesion. To delineate the size of the fetal cisterna magna, standardized measurements for the midsagittal depth of the cisterna magna were prospectively obtained on 219 consecutive antenatal sonograms in fetuses of 15 menstrual weeks or more. The cisterna magna depth measured 5 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…30 Previous studies have reported this definition to be inaccurate, and it has been shown to vary with gestational age. 31,32 The cisterna magna is a fluid-filled space that is normally continuous with the subarachnoid space of the entire PF, between the foramen magnum and the tentorium cerebelli.…”
Section: Discussionmentioning
confidence: 99%
“…30 Previous studies have reported this definition to be inaccurate, and it has been shown to vary with gestational age. 31,32 The cisterna magna is a fluid-filled space that is normally continuous with the subarachnoid space of the entire PF, between the foramen magnum and the tentorium cerebelli.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the cisterna magna can appear to be enlarged as an artifact of increasing the angle of the transducer inclination [15]. The space caudal to the cerebellar tonsils can be misinterpreted as vermian hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Enlargement of the CM (ECM), also referred to as mega CM, has historically been defined as an anteroposterior CM measurement >10 mm [3,4]. Enlargement may represent normal anatomical variation or may be pathological due to either direct or passive ECM.…”
Section: Introductionmentioning
confidence: 99%
“…The original definition of ECM in the fetal period as a diameter >10 mm is based on a small number of observations from 219 patients [3]; other studies have also evaluated relatively small numbers of patients [7], including studies that have evaluated the use of magnetic resonance imaging [8]. Prior evaluation of the CM through pregnancy has demonstrated an increase in the CM diameter with advancing gestation [9], therefore using a single value as a cut-off for determining enlargement might not be the most appropriate approach but in clinical practice the 10-mm cut-off remains the standard determinant of an enlarged CM at all gestations.…”
Section: Introductionmentioning
confidence: 99%